Blue flags fly in the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The first beaches in the Caribbean have begun flying the Blue Flag, denoting cleanliness, environmental conservation and safety. The Blue Flag International Jury has given 12 coastal sites in the Bahamas, the Dominican Republic, Jamaica and Puerto Rico th